Anion exchange membrane and preparation method thereof
By filling the surface of the porous polymer with anion exchange polymer on the surface and inside the pores of the pores, the limitations of improving the ion exchange capacity and membrane physical properties of the anion exchange membrane in the prior art are solved, and an anion exchange membrane with high ion exchange capacity and excellent appearance is achieved.
Patent Information
- Application Number
- CN202480003794.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-25
- Filing Date
- 2024-07-25
- Publication Date
- 2025-04-04
AI Technical Summary
The existing anion exchange membranes have limitations in increasing the ion exchange capacity and improving the physical properties of the membrane, especially the chemical resistance of the hydrocarbon-based anion exchange membrane is insufficient, and the film containing the support has a certain support component.
By filling the surface of the porous polymer with an anion exchange polymer on the surface and inside the pores of the pore, an anion exchange membrane is formed using a composition of crosslinked monomer and ionic monomer to improve the ion exchange capacity and mechanical strength of the membrane.
The high ion exchange capacity and excellent appearance performance of the anion exchange membrane are achieved, which reduces the sheet resistance and improves mechanical durability and chemical stability.
Smart Images

Figure CN119768455A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an anion exchange membrane and a preparation method thereof. Background Art
[0002] Ion exchange membrane refers to a synthetic resin membrane that selects cations and anions to allow only one of the ions to penetrate. Cation exchange membranes have negatively charged functional groups to allow cations to selectively penetrate, while anion exchange membranes have positively charged functional groups to allow anions to selectively penetrate. Generally speaking, ion exchange membranes require high penetration selectivity, low resistance, excellent mechanical strength, high chemical stability, etc.
[0003] This anion exchange membrane can be applied to water treatment systems such as electrodialysis, bipolar membrane electrodialysis, storage desalination, and electrodeionization, or to systems such as fuel cells, water electrolysis, reverse electrodialysis, and redox flow batteries. The system using anion exchange membrane can apply acidic or alkaline raw water to the process, and may produce acid or alkali during the process operation of raw water. Here, as anion exchange membrane, perfluorinated anion exchange membrane can be used, but due to its high price, hydrocarbon-based anion exchange membrane is applied in actual systems. However, hydrocarbon-based anion exchange membrane is limited in application process and conditions due to chemical resistance problems. In addition, since the anion exchange membrane comprising a support has a certain support fraction in its membrane, it is limited in increasing ion exchange capacity to improve membrane properties. Summary of the invention
[0004] One of the technical problems to be solved by the present application is to increase the electrolyte content in the ion exchange membrane to provide an anion exchange membrane with high ion exchange capacity and excellent appearance.
[0005] Another technical problem to be solved by the present application is to provide a method for preparing the anion exchange membrane.
[0006] According to one aspect, an anion exchange membrane is provided, comprising:
[0007] A porous polymer support; and
[0008] An electrolyte comprising an anion exchange polymer, wherein
[0009] The electrolyte is located on at least a portion of the surface and pores of the porous polymer support, and
[0010] The anion exchange polymer is a cross-linked combination product of a composition comprising a cross-linking monomer represented by the following Chemical Formula 1 and an ionic monomer represented by the following Chemical Formula 2:
[0011]
[0012] In chemical formula 1, X - is a halogen anion;
[0013] In chemical formula 2,
[0014] A is -O-, Among them, R a is hydrogen, substituted or unsubstituted C1 to C20 alkyl, or substituted or unsubstituted C5 to C40 aryl;
[0015] R1 is hydrogen, or a substituted or unsubstituted C1 to C20 alkyl group;
[0016] R2 and R3 are independently substituted or unsubstituted C1 to C20 alkyl groups, or substituted or unsubstituted C5 to C40 aryl groups;
[0017] R4 is a substituted or unsubstituted C1 to C20 alkyl group, a substituted or unsubstituted C3 to C30 cycloalkyl group, or a substituted or unsubstituted C5 to C30 aryl group;
[0018] p is 0 or 1;
[0019] q is an integer from 0 to 6;
[0020] r is an integer from 0 to 6; and
[0021] Y - It is a halogen anion.
[0022] Preferably, in the Chemical Formula 2, the R4 may be a substituted or unsubstituted C1 to C10 alkyl group, or a substituted or unsubstituted C6 to C20 aryl group.
[0023] Preferably, in the chemical formula 2, A is -O-; and R4 may be a substituted or unsubstituted C1 to C5 alkyl group, or a substituted or unsubstituted C6 to C15 aryl group.
[0024] Preferably, the ionic monomer may include:
[0025] (3-Acrylamidopropyl)trimethylammonium chloride, (3-Acrylamidopropyl)trimethylammonium bromide, (3-Acrylamidopropyl)trimethylammonium iodide;
[0026] (3-Methacrylamido)trimethylammonium chloride, (3-methacrylamido)trimethylammonium bromide, (3-methacrylamido)trimethylammonium iodide;
[0027] (2-Acryloyloxyethyl)trimethylammonium chloride, (2-acryloyloxyethyl)trimethylammonium bromide, (2-acryloyloxyethyl)trimethylammonium iodide;
[0028] (2-Methacryloyloxyethyl)trimethylammonium chloride, (2-methacryloyloxyethyl)trimethylammonium bromide, (2-methacryloyloxyethyl)trimethylammonium iodide;
[0029] N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride, N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium bromide, N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium iodide;
[0030] Benzyldimethyl[2-(2-methyl-1-oxoallyl)oxyethyl]ammonium chloride, benzyldimethyl[2-(2-methyl-1-oxoallyl)oxyethyl]ammonium bromide, benzyldimethyl[2-(2-methyl-1-oxoallyl)oxyethyl]ammonium iodide;
[0031] 2-(Acryloyloxy)-N,N-dimethyl-N-(2-methylbenzyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(2-methylbenzyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(2-methylbenzyl)ethane-1-ammonium iodide;
[0032] 2-(Acryloyloxy)-N,N-dimethyl-N-(3-methylbenzyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(3-methylbenzyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(3-methylbenzyl)ethane-1-ammonium iodide;
[0033] 2-(Acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium iodide;
[0034] 2-(Acryloyloxy)-N-(3,5-dimethylbenzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(3,5-dimethylbenzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(3,5-dimethylbenzyl)-N,N-dimethylethane-1-ammonium iodide;
[0035] 2-(Acryloyloxy)-N-(4-isopropylbenzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(4-isopropylbenzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(4-isopropylbenzyl)-N,N-dimethylethane-1-ammonium iodide;
[0036] 2-(Acryloyloxy)-N-(4-(tert-butyl)benzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(4-(tert-butyl)benzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(4-(tert-butyl)benzyl)-N,N-dimethylethane-1-ammonium iodide;
[0037] 2-(Acryloyloxy)-N-(3,5-di-tert-butylbenzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(3,5-di-tert-butylbenzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(3,5-di-tert-butylbenzyl)-N,N-dimethylethane-1-ammonium iodide;
[0038] 2-(Acryloyloxy)-N,N-dimethyl-N-(naphthalen-1-ylmethyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(naphthalen-1-ylmethyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(naphthalen-1-ylmethyl)ethane-1-ammonium iodide;
[0039] 2-(Acryloyloxy)-N((9,10-dihydropyrene-4-yl)methyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N((9,10-dihydropyrene-4-yl)methyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N((9,10-dihydropyrene-4-yl)methyl)-N,N-dimethylethane-1-ammonium iodide;
[0040] (Vinylbenzyl)trimethylammonium chloride, (vinylbenzyl)trimethylammonium bromide, (vinylbenzyl)trimethylammonium iodide; and
[0041] (2-methylvinylbenzyl)trimethylammonium chloride, (2-methylvinylbenzyl)trimethylammonium bromide, (2-methylvinylbenzyl)trimethylammonium iodide.
[0042] Preferably, the weight ratio of the crosslinking monomer to the ionic monomer may be 1:0.2 to 1:8.
[0043] The total content of the crosslinking monomer and the ionic monomer may be 30 wt % to 85 wt % based on 100 wt % in total of the composition.
[0044] Preferably, the composition further comprises a photoinitiator, wherein
[0045] The photoinitiator may be included in an amount of 0.01 wt % to 2 wt % based on 100 wt % in total of the composition.
[0046] Preferably, the porous polymer support may be a membrane structure, a non-woven fabric structure, a fabric structure or a mesh structure.
[0047] Preferably, the porous polymer support may comprise one or more polymers selected from polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polybenzimidazole, polyarylether sulfide, polyetheretherketone, polyethersulfone, polysulfone, polystyrene, polyarylethersulfone and polyetherketone.
[0048] Preferably, the porosity of the porous polymer support is 30% to 80%, and the thickness of the porous polymer support may be 10 μm to 150 μm.
[0049] Preferably, the sheet resistance (R m ) can be equal to or less than 6Ω·cm 2 :
[0050] [Formula 1]
[0051] R m (Ω·cm 2 )=(R 11 -R 12 )×S
[0052] In the formula,
[0053] R m is the sheet resistance of the anion exchange membrane,
[0054] R 11 is the conductor resistance of the anion exchange membrane,
[0055] R 12 is the resistance of 0.5M NaCl aqueous solution,
[0056] S is the area of the electrode.
[0057] Preferably, the anion exchange membrane may have an ion exchange capacity (IEC) equal to or greater than 1.5 meq / g.
[0058] Preferably, the anion exchange membrane can be used for electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization or water electrolysis.
[0059] According to another aspect, a method for preparing an anion exchange membrane is provided, which comprises the following steps, so as to prepare the anion exchange membrane:
[0060] Providing a porous polymer support;
[0061] preparing a composition for forming an anion exchange polymer, wherein the composition for forming an anion exchange polymer comprises a crosslinking monomer represented by the following chemical formula 1, an ionic monomer represented by the following chemical formula 2, a photoinitiator, and a solvent;
[0062] impregnating the porous polymer support with the anion exchange polymer-forming composition so that the composition is filled in at least a portion of the surface and pores of the porous polymer support;
[0063] Pressing a polyester base film on at least one surface of a porous polymer support filled with the composition to prepare a laminate having the polyester base film and the porous polymer support laminated thereon;
[0064] irradiating the laminate with light and causing the composition to undergo a cross-linking reaction, thereby forming an anion exchange polymer as a cross-linked product of the composition on at least a portion of the surface and inside the pores of the porous polymer support; and
[0065] The polyester base film is peeled off from the porous polymer support having the anion exchange polymer formed on at least a portion of the surface and the inside of the pores to prepare an anion exchange membrane:
[0066]
[0067] In Chemical Formula 1,
[0068] X - is a halogen anion;
[0069] In chemical formula 2,
[0070] A is -O-, Among them, R a is hydrogen, substituted or unsubstituted C1 to C20 alkyl, or substituted or unsubstituted C5 to C40 aryl;
[0071] R1 is hydrogen, or a substituted or unsubstituted C1 to C20 alkyl group;
[0072] R2 and R3 are independently substituted or unsubstituted C1 to C20 alkyl groups, or substituted or unsubstituted C5 to C40 aryl groups;
[0073] R4 is a substituted or unsubstituted C1 to C20 alkyl group, a substituted or unsubstituted C3 to C30 cycloalkyl group, or a substituted or unsubstituted C5 to C30 aryl group;
[0074] p is 0 or 1;
[0075] q is an integer from 0 to 6;
[0076] r is an integer from 0 to 6; and
[0077] Y - It is a halogen anion.
[0078] Preferably, in the step of forming the anion exchange polymer, the light is ultraviolet light, which may include the following process: the light is irradiated at 2000 mJ / cm 2 Up to 10000mJ / cm 2 irradiate with the amount of light.
[0079] The anion exchange membrane provided by the present application can achieve the following beneficial effects: because it comprises: a porous polymer support; and an electrolyte, wherein the electrolyte contains an anion exchange polymer, which is a cross-linked combination product of a composition comprising a cross-linking monomer represented by the chemical formula 1 and an ionic monomer represented by the chemical formula 2. The electrolyte wraps at least a portion of the surface and the inside of the pores of the porous support. Therefore, the anion exchange membrane increases the ion exchange capacity by increasing the content of the electrolyte in the anion exchange membrane, thereby improving the performance of the anion exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1 FIG. 1 is a schematic diagram of an anion exchange membrane according to one embodiment.
[0081] Wherein: The description of the reference numerals is as follows:
[0082] 20: porous polymer support, 21: pores
[0083] 30: Anion exchange polymer backbone with cationic functional groups
[0084] 31: Anion exchange polymer DETAILED DESCRIPTION
[0085] Hereinafter, an anion exchange membrane and a method for preparing the same according to an embodiment are described in more detail.
[0086] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as those generally understood by technicians in the technical field to which the present invention belongs. In case of conflict, the present specification including the definition shall prevail. Although methods and materials similar or identical to those described in this specification can be used for the implementation or testing of the present invention, the present invention describes suitable methods and materials. In this specification, the term "comprising" means that other constituent elements can be further included, rather than excluding other constituent elements, unless otherwise described to the contrary. In this specification, the term "these combinations" refers to a mixture or combination with one or more described constituent elements. In this specification, the term "and / or" includes any combination and all combinations of one or more items related to each other. In this specification, the term "or" refers to "and / or". In this specification, "at least one" or "one or more" in front of a constituent element can supplement the list of all constituent elements, and does not mean that the individual constituent elements described above can be supplemented. In this specification, when a constituent element is arranged "on" or "above" another constituent element, a constituent element can be directly arranged on another constituent element, or other constituent elements can be between the constituent elements. On the other hand, when a constituent element is arranged "directly" on or "over" another constituent element, there may be no constituent elements intervening therebetween. In the present specification, "~-based resin", "~-based polymer", "~-based polymer" or / and "~-based copolymer" are broad concepts, which include "~-resin", "~-polymer", "~-polymer", "~-copolymer" or / and "derivatives of~-resin, polymer, polymer or copolymer". In the present specification, the term "polymer or copolymer cross-linked by these resins" refers to "polymer or copolymer cross-linked by the aforementioned resin".
[0087] A typical anion exchange membrane has a structure in which an anion exchange polymer having a cationic functional group is arranged on the upper part of a support. The anion exchange membrane is required to have high permeation selectivity for anions, low electrical resistance, excellent mechanical strength and chemical stability.
[0088] Known anion exchange membranes include perfluorinated anion exchange membranes or hydrocarbon-based anion exchange membranes. Compared with perfluorinated anion exchange membranes, hydrocarbon-based anion exchange membranes are cheaper, but have insufficient chemical resistance. In addition, since the anion exchange membranes used for supports have a certain support fraction, they are limited in increasing the ion exchange capacity to improve the concentration and desalination performance.
[0089] The present inventors have increased the content of electrolyte in the ion exchange membrane by solving the above-mentioned problems, thereby providing an anion exchange membrane having an excellent appearance.
[0090] The anion exchange membrane according to one embodiment comprises: a porous polymer support; and an electrolyte containing an anion exchange polymer, wherein the electrolyte is located on the surface of the porous polymer support and at least a portion of the inside of the pores, and the anion exchange polymer may be a cross-linked combination product of a composition comprising a cross-linking monomer represented by the following chemical formula 1 and an ionic monomer represented by the following chemical formula 2:
[0091]
[0092]
[0093] In chemical formula 1, X - It can be a halogen anion;
[0094] In chemical formula 2,
[0095] A can be -O-, Among them, R a It may be hydrogen, a substituted or unsubstituted C1 to C20 alkyl group, or a substituted or unsubstituted C5 to C40 aryl group;
[0096] R1 may be hydrogen, or may be a substituted or unsubstituted C1 to C20 alkyl group;
[0097] R2 and R3 may be independently substituted or unsubstituted C1 to C20 alkyl groups, or substituted or unsubstituted C5 to C40 aryl groups;
[0098] R4 may be a substituted or unsubstituted C1 to C20 alkyl group, a substituted or unsubstituted C3 to C30 cycloalkyl group, or a substituted or unsubstituted C5 to C30 aryl group;
[0099] p can be 0 or 1;
[0100] q can be an integer from 0 to 6;
[0101] r may be an integer from 0 to 6; and
[0102] Y - It may be a halogen anion.
[0103] In the ionic monomer represented by Chemical Formula 2, the vinyl group is a functional group that can be cross-linked with the cross-linking monomer represented by Chemical Formula 1.
[0104] The anion exchange membrane according to an embodiment may have low sheet resistance and excellent appearance compared to an anion exchange membrane including an anion exchange polymer prepared using the cross-linking monomer represented by Chemical Formula 1 without an ionic monomer.
[0105] For example, in Chemical Formula 2, R4 may be a substituted or unsubstituted C1 to C10 alkyl group, or a substituted or unsubstituted C6 to C20 aryl group.
[0106] For example, in Chemical Formula 2, A may be -O-; and R4 may be a substituted or unsubstituted C1 to C5 alkyl group, or a substituted or unsubstituted C6 to C15 aryl group.
[0107] For example, the ionic monomer may include:
[0108] (3-Acrylamidopropyl)trimethylammonium chloride, (3-Acrylamidopropyl)trimethylammonium bromide, (3-Acrylamidopropyl)trimethylammonium iodide;
[0109] (3-Methacrylamido)trimethylammonium chloride, (3-methacrylamido)trimethylammonium bromide, (3-methacrylamido)trimethylammonium iodide;
[0110] (2-Acryloyloxyethyl)trimethylammonium chloride, (2-acryloyloxyethyl)trimethylammonium bromide, (2-acryloyloxyethyl)trimethylammonium iodide;
[0111] (2-Methacryloyloxyethyl)trimethylammonium chloride, (2-methacryloyloxyethyl)trimethylammonium bromide, (2-methacryloyloxyethyl)trimethylammonium iodide;
[0112] N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride, N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium bromide, N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium iodide;
[0113] Benzyldimethyl[2-(2-methyl-1-oxoallyl)oxyethyl]ammonium chloride, benzyldimethyl[2-(2-methyl-1-oxoallyl)oxyethyl]ammonium bromide, benzyldimethyl[2-(2-methyl-1-oxoallyl)oxyethyl]ammonium iodide;
[0114] 2-(Acryloyloxy)-N,N-dimethyl-N-(2-methylbenzyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(2-methylbenzyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(2-methylbenzyl)ethane-1-ammonium iodide;
[0115] 2-(Acryloyloxy)-N,N-dimethyl-N-(3-methylbenzyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(3-methylbenzyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(3-methylbenzyl)ethane-1-ammonium iodide;
[0116] 2-(Acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium iodide;
[0117] 2-(Acryloyloxy)-N-(3,5-dimethylbenzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(3,5-dimethylbenzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(3,5-dimethylbenzyl)-N,N-dimethylethane-1-ammonium iodide;
[0118] 2-(Acryloyloxy)-N-(4-isopropylbenzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(4-isopropylbenzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(4-isopropylbenzyl)-N,N-dimethylethane-1-ammonium iodide;
[0119] 2-(Acryloyloxy)-N-(4-(tert-butyl)benzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(4-(tert-butyl)benzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(4-(tert-butyl)benzyl)-N,N-dimethylethane-1-ammonium iodide;
[0120] 2-(Acryloyloxy)-N-(3,5-di-tert-butylbenzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(3,5-di-tert-butylbenzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(3,5-di-tert-butylbenzyl)-N,N-dimethylethane-1-ammonium iodide;
[0121] 2-(Acryloyloxy)-N,N-dimethyl-N-(naphthalen-1-ylmethyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(naphthalen-1-ylmethyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(naphthalen-1-ylmethyl)ethane-1-ammonium iodide;
[0122] 2-(Acryloyloxy)-N((9,10-dihydropyrene-4-yl)methyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N((9,10-dihydropyrene-4-yl)methyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N((9,10-dihydropyrene-4-yl)methyl)-N,N-dimethylethane-1-ammonium iodide;
[0123] (Vinylbenzyl)trimethylammonium chloride, (vinylbenzyl)trimethylammonium bromide, (vinylbenzyl)trimethylammonium iodide; and
[0124] (2-methylvinylbenzyl)trimethylammonium chloride, (2-methylvinylbenzyl)trimethylammonium bromide, (2-methylvinylbenzyl)trimethylammonium iodide.
[0125] For example, the ionic monomer may include (3-acrylamidopropyl)trimethylammonium chloride, (3-methacrylamido)trimethylammonium chloride, (2-acryloyloxyethyl)trimethylammonium chloride, (2-methacryloyloxyethyl)trimethylammonium chloride, N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride, benzyldimethyl[2-(2-methyl-1-oxoallyl)oxyethyl]ammonium chloride, (vinylbenzyl)trimethylammonium chloride, and (2-methylvinylbenzyl)trimethylammonium chloride.
[0126] The weight ratio of the crosslinking monomer to the ionic monomer may be 1:0.2 to 1:8. For example, the weight ratio of the crosslinking monomer to the ionic monomer may be 1:0.2 to 1:5, or may be 1:0.5 to 1:5. If the weight ratio of the crosslinking monomer to the ionic monomer is within the range, the anion exchange performance of the anion exchange membrane may be improved without reducing the solubility characteristics of the anion exchange polymer-forming composition.
[0127] Based on a total of 100 wt % of the composition, the total content of the crosslinking monomer and the ionic monomer may be 30 wt % to 85 wt %. For example, based on a total of 100 wt % of the composition, the total content of the crosslinking monomer and the ionic monomer may be 35 wt % to 80 wt %, or may be 40 wt % to 75 wt %. If the total content of the crosslinking monomer and the ionic monomer is less than 30 wt %, the anion exchange performance of the anion exchange membrane may decrease, and if it exceeds 85 wt %, when preparing an electrolyte solution of the composition, the solubility of the monomer constituting the anion exchange polymer may decrease.
[0128] The composition further comprises a photoinitiator, and based on a total of 100% by weight of the composition, the content of the photoinitiator can be 0.01% by weight to 2% by weight. As long as the photoinitiator is available in the art, the photoinitiator can be used without restriction, for example, it can be 2-hydroxy-2-methylpropiophenone. For example, based on a total of 100% by weight of the composition, the content of the photoinitiator can be 0.1% by weight to 1% by weight.
[0129] Figure 1 FIG. 1 is a schematic diagram of an anion exchange membrane according to one embodiment.
[0130] See also Figure 1 In the anion exchange membrane 40 according to an embodiment, the anion exchange polymer 31 having a cationic functional group is located on the surface of the porous polymer support 20 and inside the pores 21. Since the anion exchange polymer 31 having a cationic functional group is uniformly distributed on the surface of the porous polymer support 20 and inside the pores 21, a homogeneous anion exchange membrane 40 can be obtained. The structure of this anion exchange membrane 40 can have low sheet resistance and high ionic conductivity. In addition, the porous polymer support 20 can improve mechanical durability and has high dimensional stability.
[0131] The porous polymer support 20 may be in a sponge-like or three-dimensional network-like form. The porous polymer support 20 may be in a membrane structure, a non-woven fabric structure, a fabric structure or a mesh structure.
[0132] The porous polymer support 20 may include one or more polymers selected from polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polybenzimidazole, polyarylethersulfide, polyetheretherketone, polyethersulfone, polysulfone, polystyrene, polyarylethersulfone and polyetherketone. For example, the porous polymer support 20 may include one or more polymers selected from polyethylene, polypropylene and polyvinyl alcohol.
[0133] The porosity of the porous polymer support 20 can be 30% to 80%. Here, % refers to volume %. The pore size of the porous polymer support 20 refers to the average diameter when the pore is spherical, and refers to the major axis length when the pore is non-spherical. The porosity and pore size of the porous polymer support 20 can be measured from the specific surface area detection method (Brunauer, Emmett and Teller, BET) and / or the surface scanning electron microscope (Scanning Electron Microscope, SEM) image, and the porosity can be obtained by the area ratio of the cross-sectional SEM image analysis. In addition, the porosity can be calculated by using basis weight and thickness.
[0134] The thickness of the porous polymer support may be 10 μm to 150 μm. For example, the thickness of the porous polymer support may be 20 μm to 150 μm, or may be 40 μm to 150 μm, or may be 60 μm to 140 μm. Within the thickness range of the porous polymer support, sheet resistance may be reduced and ion exchange capacity may be increased.
[0135] The sheet resistance (R m ) can be equal to or less than 6Ω·cm 2 :
[0136] [Formula 1]
[0137] R m (Ω·cm 2 )=(R 11 -R 12 )×S
[0138] In the formula,
[0139] R m can be the sheet resistance of the anion exchange membrane,
[0140] R 11 can be the conductor resistance of the anion exchange membrane,
[0141] R 12 can be the resistance of 0.5M NaCl aqueous solution,
[0142] S can be the area of the electrode.
[0143] The anion exchange capacity IEC of the anion exchange membrane 40 may be equal to or greater than 1.5 meq / g.
[0144] The anion exchange membrane 40 can be used in electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization or water electrolysis.
[0145] The anion exchange membrane 40 can be used in energy systems such as fuel cells, water electrolysis, reverse electrodialysis, and redox flow batteries.
[0146] According to another embodiment, a method for preparing an anion exchange membrane comprises the following steps to prepare the anion exchange membrane: providing a porous polymer support; preparing an anion exchange polymer forming composition, wherein the anion exchange polymer forming composition comprises a cross-linking monomer represented by the following chemical formula 1, an ionic monomer represented by the following chemical formula 2, a photoinitiator, and a solvent; impregnating the porous polymer support with the anion exchange polymer forming composition to fill the composition in at least a portion of the surface of the porous polymer support and the inside of the pores. ; pressing a polyester base film onto at least one surface of a porous polymer support filled with the composition to prepare a laminate having the polyester base film and the porous polymer support laminated thereon; irradiating the laminate with light and causing the composition to undergo a cross-linking reaction to form an anion exchange polymer as a cross-linked bonding product of the composition on at least a portion of the surface and pores of the porous polymer support; and peeling off the polyester base film from the porous polymer support having the anion exchange polymer formed on at least a portion of the surface and pores to prepare an anion exchange membrane.
[0147]
[0148] In chemical formula 1, X - It can be a halogen anion;
[0149] In chemical formula 2,
[0150] A is -O-, Among them, R a It may be hydrogen, a substituted or unsubstituted C1 to C20 alkyl group, or a substituted or unsubstituted C5 to C40 aryl group;
[0151] R1 may be hydrogen, or may be a substituted or unsubstituted C1 to C20 alkyl group;
[0152] R2 and R3 may be independently substituted or unsubstituted C1 to C20 alkyl groups, or substituted or unsubstituted C5 to C40 aryl groups;
[0153] R4 may be a substituted or unsubstituted C1 to C20 alkyl group, a substituted or unsubstituted C3 to C30 cycloalkyl group, or a substituted or unsubstituted C5 to C30 aryl group;
[0154] p can be 0 or 1;
[0155] q can be an integer from 0 to 6;
[0156] r may be an integer from 0 to 6; and
[0157] Y - It may be a halogen anion.
[0158] First, a porous polymer support is provided.
[0159] The shape, structure, material, porosity, pore size and thickness of the porous polymer support are the same as those described above and will not be described in detail.
[0160] Before immersing the porous polymer support in a composition for forming an anion exchange polymer as an ion exchange resin solution so that the ion exchange resin solution wraps the pores and outer surface of the porous polymer support, it can further include immersing the porous polymer support in a surfactant solution and drying to hydrophilize the surface of the porous polymer support.
[0161] The hydrophilization can be performed according to the hydrophilization degree of the porous polymer support or the structure of the porous polymer support, and this step can be omitted if the hydrophilization degree of the porous polymer support is sufficient or the pores of the substrate are large enough to be filled with the ion exchange resin solution.
[0162] In the hydrophilization step, the immersion time may be 0.1 to 10 minutes, or 0.5 to 8 minutes. If the immersion time is less than 0.1 minutes, the surface of the porous polymer support is not sufficiently hydrophilized, resulting in the inability of the ion exchange resin solution to be filled into the pores of the porous polymer support. If the immersion time exceeds 10 minutes, problems such as reduced production speed and increased production cost may occur.
[0163] By the above-mentioned impregnation, the ion exchange resin solution is filled into the pores of the porous polymer support, thereby forming a shape in which the pores are filled. Alternatively, the outer surface of the porous polymer support may be coated with the ion exchange resin.
[0164] In addition, in the hydrophilization step, drying may be performed immediately after the immersion, and may be performed at a temperature of 40° C. to 90° C. for 1 minute to 20 minutes, or may be performed at a temperature of 40° C. to 80° C. for 1 minute to 10 minutes.
[0165] On the other hand, the surfactant solution may contain 0.001 wt % to 6 wt % of the surfactant and the remainder is the solvent, or may contain 0.01 wt % to 4 wt % of the surfactant and the remainder is the solvent, or may contain 0.05 wt % to 3 wt % of the surfactant and the remainder is the solvent.
[0166] If the content of the surfactant contained in the surfactant solution is less than 0.001 wt %, the surface of the porous polymer support is not hydrophilic, resulting in the ion exchange resin solution being unable to fill the pores of the substrate. If its content exceeds 6 wt %, the surfactant may be eluted or the filling amount of the ion exchange resin may be reduced.
[0167] As long as it is a known surfactant, the surfactant can be used without limitation, for example, one or more materials selected from dodecyl benzenesulfonic acid (DBSA), alkylbenzenesulfonic acid (ABS), linear-alkly benzenesulfonic acid (LAS), alpha-sulfonic acid (AS), alpha-olefin sulfonic acid (AOS), alcohol polyoxyethylene ether (AE) and alcohol polyoxyethylene ether sulfonic acid (AES) can be used. For example, the surfactant can be dodecyl benzenesulfonic acid.
[0168] When the hydrophobic part of surfactant is attached to the surface of hydrophobic porous polymer support by hydrophobicity-hydrophobic interaction (hydrophobic-hydrophobic interaction), the hydrophilic part of surfactant covers the surface of porous polymer support and replaces the hydrophobicity on the surface, so as to achieve hydrophilization. Here, surfactant can not only make the outer surface hydrophilization of porous polymer support, but also can make the surface hydrophilization of whole internal pores. However, if the hydrophilization degree of porous polymer support is enough, or if the pore of porous polymer support is large enough, so as to be able to fill anion exchange polymer to form composition, then it can be omitted.
[0169] Next, an anion exchange polymer-forming composition as an ion exchange resin solution is prepared, which includes a crosslinking monomer represented by the chemical formula 1 as an electrolyte monomer having a cationic group, an ionic monomer represented by the chemical formula 2, a photoinitiator, and a solvent.
[0170] The ion exchange resin solution is irradiated with ultraviolet rays to crosslink the crosslinking monomer represented by Chemical Formula 1 as an electrolyte monomer having a cationic group and the ionic monomer represented by Chemical Formula 2, thereby forming a crosslinked bonded product.
[0171] In the present specification, "crosslinked product" refers to all initial reaction products, intermediate reaction products, final products and unreacted products, in addition to the polymer formed by crosslinking the crosslinking monomer represented by Chemical Formula 1 and the ionic monomer represented by Chemical Formula 2.
[0172] The total content of the crosslinking monomer represented by Chemical Formula 1 and the ionic monomer represented by Chemical Formula 2, and the type and content of the photoinitiator are the same as those described above and will not be described in detail.
[0173] As long as the solvent is available in the art, the solvent can be used without limitation, for example, it can be water, a water-soluble solvent such as methanol or ethanol, or distilled water. The solvent can be contained in an amount remaining after removing the crosslinking monomer represented by Chemical Formula 1, the ionic monomer represented by Chemical Formula 2, and the photoinitiator from the anion exchange polymer-forming composition.
[0174] The polyester base film is pressed onto at least one surface of the porous polymer support filled with the composition to prepare a laminated body in which the polyester base film and the porous polymer support are laminated.
[0175] The polyester base film can be pressed onto the upper surface or / and the lower surface of the porous polymer support by roll calendering. The polyester base film can be a polyethylene terephthalate film.
[0176] The thickness of the polyester base film may be 10 μm to 150 μm, for example, 20 μm to 120 μm, or 30 μm to 100 μm. If the thickness of the polyester base film is less than 10 μm, lamination defects such as wrinkles on the film may occur when laminated with a support filled with an anion exchange polymer. If the thickness of the polyester base film exceeds 150 μm, during the cross-linking reaction described later, the thickness of the polyester base film is too large, and light may not be sufficiently irradiated to the porous polymer support, resulting in that the cross-linking reaction may not sufficiently occur.
[0177] The surface of the polyester base film in contact with the porous polymer support may be untreated or may be subjected to demolding treatment. By using such a film, the combination of the polyester base film and the hydrophilic anion exchange polymer is hindered, thereby preventing the anion exchange polymer from falling off the surface of the support. The pressing may be performed at a temperature of 10° C. to 35° C., for example, 15° C. to 30° C., and a pressure of about 0 bar to 5 bar. The pressure may be appropriately adjusted in consideration of the thickness of the porous polymer support and the thickness of the polyester base film.
[0178] Next, the laminate is irradiated with light to cause a cross-linking reaction of the composition, thereby forming an anion exchange polymer as a cross-linked product of the composition on the surface of the porous polymer support and inside the pores.
[0179] In the step of forming the anion exchange polymer, the light may be ultraviolet light. For example, UVA, UVB, UVC, or / and UVV may be used.
[0180] The following process may be included: the light may use UVC and emit light at 2000mJ / cm 2 Up to 10000mJ / cm 2 For example, the light may be UVC, and the light may be irradiated at 2000 mJ / cm 2 Up to 8000mJ / cm 2 When light irradiation is performed under such conditions, an ion exchange membrane having improved ion exchange capacity can be prepared.
[0181] Finally, the polyester base film is peeled off from the porous polymer support having the anion exchange polymer formed on the surface and inside the pores to prepare an anion exchange membrane. The peeling can be completed by pulling the polyester base film on the porous polymer support in opposite directions using a peeling roller.
[0182] The anion exchange membrane prepared according to the preparation method may include a porous polymer support; and an anion exchange polymer, wherein the anion exchange polymer is an ion exchange resin that fills the pores of the porous polymer support and wraps the outer surface of the substrate.
[0183] The average thickness of the anion exchange membrane may be 10 μm to 200 μm, for example, 12 μm to 150 μm. If the average thickness is less than 10 μm, the durability of the anion exchange membrane is reduced, resulting in a risk of membrane damage during operation, and desalination and concentration performance may be reduced due to the penetration of unnecessary salts. If the average thickness exceeds 200 μm, the sheet resistance increases, resulting in an increase in power consumption required during operation, and desalination and concentration performance may be reduced.
[0184] In addition, the anion exchange membrane may have an ion exchange capacity (IEC) of 1.5 meq / g or more, or 1.6 meq / g or more.
[0185] In this specification, "substitution" means that one or more hydrogens in the unsubstituted mother group are exchanged for another atom or functional group and induced. Unless otherwise specified, when a functional group is considered to be "substituted", it means that the functional group is substituted with one or more substituents selected from alkyl having 1 to 20 carbon atoms, alkenyl having 2 to 20 carbon atoms, alkynyl having 2 to 20 carbon atoms, cycloalkyl having 3 to 30 carbon atoms, cycloalkenyl having 3 to 30 carbon atoms, and aryl having 6 to 40 carbon atoms. When a functional group is described as "selectively substituted", it means that the functional group can be substituted with the substituent.
[0186] In this specification, the C1 to C20 alkyl group refers to, for example, straight-chain alkyl groups such as methyl, ethyl, hexyl, octyl, and decyl; branched-chain alkyl groups such as isopropyl, tert-butyl, neopentyl, and hexyl. Among them, in consideration of the convenience of purchasing raw materials and the availability of products, it can be methyl or ethyl. One or more hydrogen atoms in the alkyl group may be substituted with a substituent as defined in the aforementioned "substituted".
[0187] In the present specification, C3 to C30 cycloalkyl refers to a cyclic alkyl group, such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, etc. One or more hydrogen atoms in the cycloalkyl group may be substituted with a substituent as defined in the aforementioned "substituted".
[0188] In the present specification, the C5 to C40 aryl group refers to an aromatic system containing one or more benzene rings, such as phenyl, naphthyl, etc. One or more hydrogen atoms in the aryl group may be substituted with a substituent as defined in the aforementioned "substituted".
[0189] In this specification, the halogen anion may include: F - , Cl - Br - ,I - wait.
[0190] Hereinafter, the present invention will be described by the following examples. At this time, the following examples are only used to describe the present invention, and the right scope of the present invention is not limited to the following examples.
[0191] [Example]
[0192] Preparation Example 1: Preparation of cross-linking monomer
[0193] A solution of 4-vinylbenzyl chloride dissolved in ethyl acetate was added to a solution of 1,4-diazabicyclo[2,2,2]octane dissolved in methanol so that the molar ratio of vinylbenzyl chloride to 1,4-diazabicyclo[2,2,2]octane was 2:1, and stirred under an inert atmosphere at room temperature to prepare a mixture. The mixture was filtered, washed with methanol, and then vacuum dried at room temperature (25° C.) to obtain a crosslinking monomer represented by the following chemical formula 1-1.
[0194] <Chemical Formula 1-1>
[0195]
[0196] Example 1: Preparation of anion exchange membrane
[0197] A polypropylene (PP) porous polymer support (porosity: 51%) having a thickness of 100 μm was prepared. The porous polymer support was immersed in a 1 wt % aqueous solution of dodecylbenzenesulfonic acid for 10 minutes and then dried in a hot air oven at 70° C. for 10 minutes to hydrophilize the porous polymer support. The hydrophilized porous polymer support was immersed in an anion exchange polymer forming composition as an ion exchange resin solution for 5 minutes to fill the ion exchange resin solution in the porous polymer support.
[0198] At this time, the anion exchange polymer forming composition is prepared by mixing 20 weight % of the crosslinking monomer of Chemical Formula 1-1 obtained according to Preparation Example 1, 40 weight % of the ionic monomer of N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride, 0.5 weight % of the photoinitiator of 2-hydroxy-2-methylpropiophenone (manufactured by Ciba Corporation) and the remaining amount of distilled water.
[0199] The polypropylene porous polymer support is impregnated with the anion exchange polymer forming composition to fill the composition on the surface and inside the pores of the porous polymer support. The porous polymer support filled with the composition is put into a pressing roller, and a polyester film with a thickness of 50 μm is pressed on the upper and lower surfaces of the porous polymer support at room temperature (25°C) to prepare a laminated body laminated with the polyester film and the porous polymer support. UVC ultraviolet rays are used at 3000 mJ / cm 2 The laminate is irradiated with a light amount of 100 to form an anion exchange polymer as a cross-linked product of the composition on the surface and inside the pores of the porous polymer support. The polyester base film is peeled off from the porous polymer support having the anion exchange polymer formed on the surface and inside the pores to prepare an anion exchange membrane.
[0200] Example 2: Preparation of anion exchange membrane
[0201] An anion exchange membrane was prepared in the same manner as in Example 1 except that 40 wt % of (2-acryloyloxyethyl)trimethylammonium chloride was used as the ionic monomer in the anion exchange polymer-forming composition.
[0202] Example 3: Preparation of anion exchange membrane
[0203] An anion exchange membrane was prepared in the same manner as in Example 1, except that 40 wt % of (3-acrylamidopropyl)trimethylammonium chloride was used as the ionic monomer in the anion exchange polymer-forming composition.
[0204] Example 4: Preparation of anion exchange membrane
[0205] An anion exchange membrane was prepared in the same manner as in Example 1 except that 40 wt % of 2-(acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium chloride was used as the ionic monomer in the anion exchange polymer-forming composition.
[0206] Example 5: Preparation of anion exchange membrane
[0207] An anion exchange membrane was prepared in the same manner as in Example 1, except that 40 wt % of (vinylbenzyl)trimethylammonium chloride was used as the ionic monomer in the anion exchange polymer-forming composition.
[0208] Example 6: Preparation of anion exchange membrane
[0209] An anion exchange membrane was prepared in the same manner as in Example 1 except that a polypropylene (PP) porous polymer support having a thickness of 60 μm (porosity: 55%) was used.
[0210] Example 7: Preparation of anion exchange membrane
[0211] An anion exchange membrane was prepared in the same manner as in Example 1 except that a polyvinyl alcohol (PVA) porous polymer support having a thickness of 125 μm (porosity: 75%) was used.
[0212] Example 8: Preparation of anion exchange membrane
[0213] An anion exchange membrane was prepared in the same manner as in Example 1, except that 50 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained according to Preparation Example 1 and 10 wt % of an ionic monomer of N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride were used in the anion exchange polymer-forming composition.
[0214] Example 9: Preparation of anion exchange membrane
[0215] An anion exchange membrane was prepared in the same manner as in Example 1 except that 50 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained in Preparation Example 1 and 10 wt % of the ionic monomer of (2-acryloyloxyethyl)trimethylammonium chloride were used in the anion exchange polymer-forming composition.
[0216] Example 10: Preparation of anion exchange membrane
[0217] An anion exchange membrane was prepared in the same manner as in Example 1 except that 50 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained in Preparation Example 1 and 10 wt % of the ionic monomer of (3-acrylamidopropyl)trimethylammonium chloride were used in the anion exchange polymer-forming composition.
[0218] Example 11: Preparation of anion exchange membrane
[0219] An anion exchange membrane was prepared in the same manner as in Example 1, except that 50 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained according to Preparation Example 1 and 10 wt % of the ionic monomer of 2-(acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium chloride were used in the anion exchange polymer-forming composition.
[0220] Example 12: Preparation of anion exchange membrane
[0221] An anion exchange membrane was prepared in the same manner as in Example 1 except that 50 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained in Preparation Example 1 and 10 wt % of an ionic monomer of (vinylbenzyl)trimethylammonium chloride were used in the anion exchange polymer-forming composition.
[0222] Example 13: Preparation of anion exchange membrane
[0223] An anion exchange membrane was prepared in the same manner as in Example 1, except that 10 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained according to Preparation Example 1 and 50 wt % of an ionic monomer of N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride were used in the anion exchange polymer-forming composition.
[0224] Example 14: Preparation of anion exchange membrane
[0225] An anion exchange membrane was prepared in the same manner as in Example 1 except that 10 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained in Preparation Example 1 and 50 wt % of the ionic monomer of (2-acryloyloxyethyl)trimethylammonium chloride were used in the anion exchange polymer-forming composition.
[0226] Example 15: Preparation of anion exchange membrane
[0227] An anion exchange membrane was prepared in the same manner as in Example 1 except that 10 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained in Preparation Example 1 and 50 wt % of the ionic monomer of (3-acrylamidopropyl)trimethylammonium chloride were used in the anion exchange polymer-forming composition.
[0228] Example 16: Preparation of anion exchange membrane
[0229] An anion exchange membrane was prepared in the same manner as in Example 13, except that 10 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained according to Preparation Example 1 and 50 wt % of the ionic monomer of 2-(acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium chloride were used in the anion exchange polymer forming composition.
[0230] Example 17: Preparation of anion exchange membrane
[0231] An anion exchange membrane was prepared in the same manner as in Example 13 except that 10 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained in Preparation Example 1 and 50 wt % of the ionic monomer of (vinylbenzyl)trimethylammonium chloride were used in the anion exchange polymer-forming composition.
[0232] Comparative Example 1: Preparation of anion exchange membrane
[0233] An anion exchange membrane was prepared in the same manner as in Example 1 except that 60 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained in Preparation Example 1 was used in the anion exchange polymer-forming composition without the ionic monomer.
[0234] Comparative Example 2: Preparation of anion exchange membrane
[0235] An anion exchange membrane was prepared in the same manner as in Example 1, except that 6 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained according to Preparation Example 1 and 54 wt % of the ionic monomer of N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride were used in the anion exchange polymer-forming composition.
[0236] Comparative Example 3: Preparation of anion exchange membrane
[0237] An anion exchange membrane was prepared in the same manner as in Example 1, except that 55 wt % of the crosslinking monomer of Chemical Formula 1-1 obtained according to Preparation Example 1 and 5.5 wt % of the ionic monomer of N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride were used in the anion exchange polymer-forming composition.
[0238] Evaluation Example 1: Physical Property Evaluation of Ion Exchange Membranes
[0239] The anion exchange membranes prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were tested by using the following methods to evaluate their physical properties. The evaluation results are shown in Table 1 below.
[0240] (1) Sheet resistance (Ω·cm) 2 )
[0241] The samples were prepared by cutting each anion exchange membrane into a size of 5 cm×5 cm. The samples were immersed in a 0.5 M NaCl aqueous solution for 24 hours. The samples were placed between the electrodes for sheet resistance measurement, and the wire resistance R of the anion exchange membrane was measured by using an LCR meter (E4908A, Agilent). 11 and the resistance R of 0.5M NaCl aqueous solution 12 The measured resistance value R 11 , R 12 Substitute into the following formula 1 to obtain the sheet resistance Rm.
[0242] [Formula 1]
[0243] R m (Ω·cm 2 )=(R 11 -R 12 )×S
[0244] In the formula,
[0245] R m is the sheet resistance of the anion exchange membrane,
[0246] R 11 is the conductor resistance of the anion exchange membrane,
[0247] R 12 is the resistance of 0.5M NaCl aqueous solution,
[0248] S is the area of the electrode.
[0249] (2) Ion Exchange Capacity (IEC, meq / g)
[0250] Prepare the sample by cutting each anion exchange membrane into a size of 5cm×5cm. Wash the sample with distilled water and then use a paper towel to remove extra moisture. Fill 70ml of 1M NaCl solution in a vial, then place the sample to remove moisture in a 1M NaCl solution, immerse for 12 hours or more, and perform a pretreatment. Then, wash the sample that has completed the pretreatment several times with distilled water, and use a paper towel to remove extra moisture. Fill 70ml of 0.5M Na2CO3 solution in a vial, then place the sample to remove moisture in a 0.5M Na2CO3 solution, immerse for 12 hours or more, and perform a secondary pretreatment. Then, remove the sample that has completed the secondary pretreatment from the vial, and titrate the remaining solution with 0.01M AgNO3 solution, and record the volume of the AgNO3 solution put in the titration process. Wash the sample several times with distilled water, and then dry it in a hot air oven at 80°C for 15 minutes. After drying, measure the weight of the dried anion exchange membrane. The measured weight of the dried anion exchange membrane was substituted into the following Formula 2 to obtain the ion exchange capacity (IEC).
[0251] [Formula 2]
[0252] IEC (meq / g) = (volume of titration reagent (ml) × 0.01) / weight of dried anion exchange membrane (g)
[0253] (3) Appearance evaluation
[0254] For each anion exchange membrane, its appearance was observed with the naked eye, and evaluated according to the following judgment criteria.
[0255] Good: No cracks or peeling on the surface
[0256] Defective: Surface cracks or peeling
[0257]
Table 1
[0258]
[0259] Referring to Table 1, it can be confirmed that the anion exchange membranes of Examples 1 to 17 have a sheet resistance equal to or less than 6 Ω·cm 2 The ion exchange capacity was equal to or greater than 1.5 meq / g and was excellent, and the appearance was good. In comparison, it was confirmed that the sheet resistance of the ion exchange membrane of Comparative Example 1, which did not use an ionic monomer, was as high as 6.3 Ω·cm 2, and cracks occurred on the surface, with a poor appearance. It can be confirmed that the ion exchange membrane of Comparative Example 2 uses a composition for forming an anion exchange polymer prepared by a weight ratio of 1:9 for a cross-linking monomer of Chemical Formula 1-1 obtained according to Preparation Example 1 and an ionic monomer, and the ion exchange capacity of the ion exchange membrane of Comparative Example 2 is low, which is 1.4 meq / g, and electrolyte stripping occurred on the surface, with a poor appearance. It can be confirmed that the ion exchange membrane of Comparative Example 3 uses a composition for forming an anion exchange polymer prepared by a weight ratio of 1:0.1 for a cross-linking monomer of Chemical Formula 1-1 obtained according to Preparation Example 1 and an ionic monomer, and the sheet resistance of the ion exchange membrane of Comparative Example 3 is as high as 6.1Ω·cm 2 , and cracks occurred on the surface, with a poor appearance.
[0260] Thus, the anion exchange membranes of Examples 1 to 17 can provide anion exchange membranes having high ion exchange capacity and good appearance.
[0261] As described above, an exemplary embodiment is described in detail with reference to the accompanying drawings, but the inventive concept is not limited to these examples. For a person skilled in the art of the inventive concept, it is obvious that various variations or modifications can be derived within the scope of the technical concept described in the patent claims, and these variations or modifications also belong to the technical scope of the inventive concept.
Claims
1. An anion exchange membrane comprising: A porous polymer support; and An electrolyte containing an anion exchange polymer, in: The electrolyte is located on the surface of the porous polymer support and at least a portion of the pores. The anion exchange polymer is a cross-linked combination product of a composition comprising a cross-linking monomer represented by the following Chemical Formula 1 and an ionic monomer represented by the following Chemical Formula 2: In Chemical Formula 1, X - is a halogen anion; In chemical formula 2, A is -O-, Among them, R a is hydrogen, substituted or unsubstituted C1 to C20 alkyl, or substituted or unsubstituted C5 to C40 aryl; R1 is hydrogen, or a substituted or unsubstituted C1 to C20 alkyl group; R2 and R3 are independently substituted or unsubstituted C1 to C20 alkyl groups, or substituted or unsubstituted C5 to C40 aryl groups; R4 is a substituted or unsubstituted C1 to C20 alkyl group, a substituted or unsubstituted C3 to C30 cycloalkyl group, or a substituted or unsubstituted C6 to C30 aryl group; p is 0 or 1; q is an integer from 0 to 6; r is an integer from 0 to 6; and Y - It is a halogen anion.
2. The anion exchange membrane according to claim 1, wherein In the Chemical Formula 2, the R4 is a substituted or unsubstituted C1 to C10 alkyl group, or a substituted or unsubstituted C6 to C20 aryl group.
3. The anion exchange membrane according to claim 1, wherein In the chemical formula 2, The A is -O-; The R4 is a substituted or unsubstituted C1 to C5 alkyl group, or a substituted or unsubstituted C6 to C15 aryl group.
4. The anion exchange membrane according to claim 1, wherein The ionic monomer comprises: (3-Acrylamidopropyl)trimethylammonium chloride, (3-Acrylamidopropyl)trimethylammonium bromide, (3-Acrylamidopropyl)trimethylammonium iodide; (3-Methacrylamido)trimethylammonium chloride, (3-methacrylamido)trimethylammonium bromide, (3-methacrylamido)trimethylammonium iodide; (2-Acryloyloxyethyl)trimethylammonium chloride, (2-acryloyloxyethyl)trimethylammonium bromide, (2-acryloyloxyethyl)trimethylammonium iodide; (2-Methacryloyloxyethyl)trimethylammonium chloride, (2-methacryloyloxyethyl)trimethylammonium bromide, (2-methacryloyloxyethyl)trimethylammonium iodide; N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium chloride, N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium bromide, N-(2-acryloyloxyethyl)-N-benzyl-N,N-dimethylammonium iodide; Benzyldimethyl[2-(2-methyl-1-oxoallyl)oxyethyl]ammonium chloride, benzyldimethyl[2-(2-methyl-1-oxoallyl)oxyethyl]ammonium bromide, benzyldimethyl[2-(2-methyl-1-oxoallyl)oxyethyl]ammonium iodide; 2-(Acryloyloxy)-N,N-dimethyl-N-(2-methylbenzyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(2-methylbenzyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(2-methylbenzyl)ethane-1-ammonium iodide; 2-(Acryloyloxy)-N,N-dimethyl-N-(3-methylbenzyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(3-methylbenzyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(3-methylbenzyl)ethane-1-ammonium iodide; 2-(Acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(4-methylbenzyl)ethane-1-ammonium iodide; 2-(Acryloyloxy)-N-(3,5-dimethylbenzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(3,5-dimethylbenzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(3,5-dimethylbenzyl)-N,N-dimethylethane-1-ammonium iodide; 2-(Acryloyloxy)-N-(4-isopropylbenzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(4-isopropylbenzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(4-isopropylbenzyl)-N,N-dimethylethane-1-ammonium iodide; 2-(Acryloyloxy)-N-(4-(tert-butyl)benzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(4-(tert-butyl)benzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(4-(tert-butyl)benzyl)-N,N-dimethylethane-1-ammonium iodide; 2-(Acryloyloxy)-N-(3,5-di-tert-butylbenzyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N-(3,5-di-tert-butylbenzyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N-(3,5-di-tert-butylbenzyl)-N,N-dimethylethane-1-ammonium iodide; 2-(Acryloyloxy)-N,N-dimethyl-N-(naphthalen-1-ylmethyl)ethane-1-ammonium chloride, 2-(Acryloyloxy)-N,N-dimethyl-N-(naphthalen-1-ylmethyl)ethane-1-ammonium bromide, 2-(Acryloyloxy)-N,N-dimethyl-N-(naphthalen-1-ylmethyl)ethane-1-ammonium iodide; 2-(Acryloyloxy)-N((9,10-dihydropyrene-4-yl)methyl)-N,N-dimethylethane-1-ammonium chloride, 2-(Acryloyloxy)-N((9,10-dihydropyrene-4-yl)methyl)-N,N-dimethylethane-1-ammonium bromide, 2-(Acryloyloxy)-N((9,10-dihydropyrene-4-yl)methyl)-N,N-dimethylethane-1-ammonium iodide; (Vinylbenzyl)trimethylammonium chloride, (vinylbenzyl)trimethylammonium bromide, (vinylbenzyl)trimethylammonium iodide; and (2-methylvinylbenzyl)trimethylammonium chloride, (2-methylvinylbenzyl)trimethylammonium bromide, (2-methylvinylbenzyl)trimethylammonium iodide.
5. The anion exchange membrane according to claim 1, wherein The weight ratio of the crosslinking monomer to the ionic monomer is 1:0.2 to 1:
8.
6. The anion exchange membrane according to claim 1, wherein The total content of the crosslinking monomer and the ionic monomer is 30 wt % to 85 wt % based on 100 wt % in total of the composition.
7. The anion exchange membrane according to claim 1, wherein The composition further comprises a photoinitiator, wherein the content of the photoinitiator is 0.01 wt % to 2 wt % based on 100 wt % of the composition in total.
8. The anion exchange membrane according to claim 1, wherein The porous polymer support is a membrane structure, a non-woven fabric structure, a fabric structure or a mesh structure.
9. The anion exchange membrane according to claim 1, wherein The porous polymer support comprises one or more polymers selected from polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polybenzimidazole, polyarylether sulfide, polyetheretherketone, polyethersulfone, polysulfone, polystyrene, polyarylethersulfone and polyetherketone.
10. The anion exchange membrane according to claim 1, wherein The porosity of the porous polymer support is 30% to 80%, and the thickness of the porous polymer support is 10 μm to 150 μm.
11. The anion exchange membrane according to claim 1, wherein The sheet resistance (R m ) is equal to or less than 6Ω·cm 2 : [Formula 1] R m (Ω·㎝ 2 )=(R 11 -R 12 )×S In the formula, R m is the sheet resistance of the anion exchange membrane, R 11 is the conductor resistance of the anion exchange membrane, R 12 is the resistance of 0.5M NaCl aqueous solution, S is the area of the electrode.
12. The anion exchange membrane according to claim 1, wherein The anion exchange membrane has an ion exchange capacity (IEC) equal to or greater than 1.5 meq / g.
13. The anion exchange membrane according to claim 1, wherein The anion exchange membrane is used in electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization or water electrolysis system.
14. A method for preparing an anion exchange membrane, comprising the following steps: Thus, the anion exchange membrane according to any one of claims 1 to 13 is prepared by providing a porous polymer support; preparing a composition for forming an anion exchange polymer, wherein the composition for forming an anion exchange polymer comprises a crosslinking monomer represented by the following chemical formula 1, an ionic monomer represented by the following chemical formula 2, a photoinitiator, and a solvent; impregnating the porous polymer support with the anion exchange polymer-forming composition so that the composition is filled in at least a portion of the surface and pores of the porous polymer support; Pressing a polyester base film on at least one surface of a porous polymer support filled with the composition to prepare a laminate having the polyester base film and the porous polymer support laminated thereon; irradiating the laminate with light and causing the composition to undergo a cross-linking reaction, thereby forming an anion exchange polymer as a cross-linked product of the composition on at least a portion of the surface and inside the pores of the porous polymer support; and The polyester base film is peeled off from the porous polymer support having the anion exchange polymer formed on at least a portion of the surface and the inside of the pores to prepare an anion exchange membrane: In Chemical Formula 1, X - is a halogen anion; In chemical formula 2, A is -O-, Among them, R a is hydrogen, substituted or unsubstituted C1 to C20 alkyl, or substituted or unsubstituted C5 to C40 aryl; R1 is hydrogen, or a substituted or unsubstituted C1 to C20 alkyl group; R2 and R3 are independently substituted or unsubstituted C1 to C20 alkyl groups, or substituted or unsubstituted C5 to C40 aryl groups; R4 is a substituted or unsubstituted C1 to C20 alkyl group, a substituted or unsubstituted C3 to C30 cycloalkyl group, or a substituted or unsubstituted C5 to C30 aryl group; p is 0 or 1; q is an integer from 0 to 6; r is an integer from 0 to 6; and Y - It is a halogen anion.
15. The method for preparing an anion exchange membrane according to claim 14, wherein: In the step of forming an anion exchange polymer, the light is ultraviolet light, and the process includes the following: The light is 2000mJ / cm 2 Up to 10000mJ / cm 2 irradiate with the amount of light.